2020
DOI: 10.1111/bjhp.12425
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19: Concerns and behaviours in Croatia

Abstract: Objectives. The COVID-19 pandemic has created uncertainty that has heightened fear and worry worldwide, thus elevating the potential for a growth in anxiety. This study aims to examine changes in levels of COVID-19 concern and safety behaviours among persons living in Croatia during the period in which the first COVID-19 case was identified and when the country recorded its first fatality. These changes were examined with respect to gender and family circumstances. Design. The repeated cross-sectional data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 6 publications
7
65
0
2
Order By: Relevance
“…To date, we have published 17 COVID-19 papers (Bacon & Corr, 2020;Gibson Miller et al, 2020;Grover, McClelland, & Furnham, 2020;Horesh, Kapel Lev-Ari, & Hasson-Ohayon, 2020;Howard, 2020;Lades, Laffan, Daly, & Delaney, 2020;Lauri Korajlija & Jokic-Begic, 2020;Lin et al, 2020;Marinthe, Brown, Delouvee, & Jolley, 2020;McElroy et al, 2020;Niepel, Kranz, Borgonovi, Emslander, & Greiff, 2020;Norman, Wilding, & Conner, 2020;Olagoke, Olagoke, & Hughes, 2020;Rubaltelli, Tedaldi, Orabona, & Scrimin, 2020;Shevlin et al, 2020;Williams et al, 2020), which have addressed a variety of topics including: the use theoretical models (COM-B and social cognition models) to understand and predict COVID-19 health behaviours (Gibson Miller et al, 2020;Lin et al, 2020;Norman et al, 2020), risk perception (Niepel et al, 2020;Olagoke et al, 2020), and psychological distress (Horesh et al, 2020;Lades et al, 2020;McElroy et al, 2020;Shevlin et al, 2020). presented a systematic method for rapidly responding to priority SARS-CoV-2 policy questions.…”
Section: Bjhp: Covid-19 Health Psychology Researchmentioning
confidence: 99%
“…To date, we have published 17 COVID-19 papers (Bacon & Corr, 2020;Gibson Miller et al, 2020;Grover, McClelland, & Furnham, 2020;Horesh, Kapel Lev-Ari, & Hasson-Ohayon, 2020;Howard, 2020;Lades, Laffan, Daly, & Delaney, 2020;Lauri Korajlija & Jokic-Begic, 2020;Lin et al, 2020;Marinthe, Brown, Delouvee, & Jolley, 2020;McElroy et al, 2020;Niepel, Kranz, Borgonovi, Emslander, & Greiff, 2020;Norman, Wilding, & Conner, 2020;Olagoke, Olagoke, & Hughes, 2020;Rubaltelli, Tedaldi, Orabona, & Scrimin, 2020;Shevlin et al, 2020;Williams et al, 2020), which have addressed a variety of topics including: the use theoretical models (COM-B and social cognition models) to understand and predict COVID-19 health behaviours (Gibson Miller et al, 2020;Lin et al, 2020;Norman et al, 2020), risk perception (Niepel et al, 2020;Olagoke et al, 2020), and psychological distress (Horesh et al, 2020;Lades et al, 2020;McElroy et al, 2020;Shevlin et al, 2020). presented a systematic method for rapidly responding to priority SARS-CoV-2 policy questions.…”
Section: Bjhp: Covid-19 Health Psychology Researchmentioning
confidence: 99%
“…To date (May 25, 2020), the number of patients with COVID-19 in Croatia is among the lowest in Europe (542/million inhabitants, fatality rate is 23/million), a trend that has been attributed to the implementation of quarantine-like measures at an early stage. Research examining psychological reactions to the COVID-19 pandemic in Croatia [ 10 ] demonstrated a dramatic increase in concern and safety behaviours among participants during the three-week period between the first identified case and the first fatality. Interestingly, there is a discordance between those who are at most risk for serious consequences of the disease and those who are at greatest risk for maladaptive anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we also hypothesized (2) that high levels of concern and worry for COVID-19 could have an impact on the protective behaviors ( Brooks et al, 2020 ; Li et al, 2020c ) by enhancing an abnormal illness behavior ( Lipowski, 1987 ) toward fueling hypochondriacal concerns or avoid behavioral recommendations. In fact, recent studies limited to parents and families, suggest that anxiety levels are connected to safety behaviors, but the health risks and fear connected to COVID-19 influence the rates of stress ( Lauri Korajlija and Jokic-Begic, 2020 ; Spinelli et al, 2020 ). Most of the studies concerning previous pandemics had focused on either the cognitive aspects related to what the population knew about the illness and what people really did to prevent the spread of the pandemic ( Barr et al, 2008 ), or on the affective aspects of the disaster, investigating post-traumatic stress disorder (PTSD), depression, or anxiety ( Goodwin et al, 2011 ; Karademas et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%